Analytical model of asymmetrical Mixed-Mode Bending test of adhesively bonded GFRP joint (Fracture and Structural Integrity, 2015)
This paper presents new analytical model of asymmetric mixed-mode bending (MMB) specimen ofadhesively bonded pultruded GFRP joints. An easily applicable relationship for the calculation of the strainenergy release rate of the asymmetric MMB specimens is proposed based on the beam theory. The model iscapable to analyze stacking sequence as well as various crack propagation paths. In the paper the effect of thevarious fiber bridging length and different crack propagation paths is analyzed analytically and supported byexperimental results. The methodology and results presented in this paper could be utilized for the design ofboth joint geometry and lay-up of the laminates constituting the joint or for the prediction of the fracturebehavior of such structures.
Keywords: GFRP materials